Mutual learning: exploring collaboration, knowledge and roles in the development of recovery-oriented services. A hermeneutic-phenomenological study - Trude Klevan (Taylor & Francis Group, 2021)
Purpose The concept of recovery is commonly described as multifaceted and contested in the field of mental health and substance abuse. The aim of this study is to explore how understandings of recovery and recovery orientation of services are developed through daily practices and collaboration between service users and professionals. Methods Eight pairs of participants were interviewed together, in accordance with the dyadic interview method. The dyads/pairs consisted of service users and professional helpers. A collaborative hermeneutic-phenomenological analysis was used to analyse data. Results Data were analysed into three overarching and entangled themes, exploring how recovery-oriented collaboration and knowledge encompasses (a) recovery as relational processes. These processes are entangled with (b) recovery as situated in time and place. Furthermore, relational processes and dimensions of time and place are situated in and supported or hindered by (c) recovery orientation as part of the municipal policies, understood as the regulations, frameworks and decisions guiding mental health and substance abuse services in the municipality. Conclusions The further development of recovery-oriented services should focus on facilitating open-ended and flexible ways of developing practices and relationships. This involves recognizing how relationships contribute to the development of knowledge and practices.